Development and characterization of adhesives from soda bamboo lignin / Syaiful Osman - Osman, Syaiful (Institute of Graduate Studies, UiTM, 2018)
Bamboo has great potential to be utilized for various purposes. It has always been associated with traditional way of Malaysian rural lifestyle. Nevertheless, time is changing and sustainability issue has increased the popularity of bamboo as sustainable supply for valuable chemical that are mostly derived from non-renewable resources nowadays. The aims of current study were, (1) to evaluate the physicochemical characteristic of four Malaysian bamboo species that is Semantan (Gigantochloa scortechinii), Beting (Gigantochloa levis), Lemang (Schizostachyum brachyladum) and Akar (Bambusa vulgaris) (2) to determine the properties lignin extracted from Malaysian bamboo and subsequently (3) to develop lignin phenol formaldehyde adhesive resins and characterize its physical, chemical and mechanical properties. Lignin was obtained from bamboo via soda pulping method using autoclave at elevated temperature and pressure. For the synthesis of lignin phenol formaldehyde, two types of bamboo lignin namely Semantan and Beting bamboo were chosen with percentage of lignin to phenol replacement were 5%, 10%, 15% and 20%. Results indicated that there was little variation in terms of extractive and major chemical composition regardless of differences in terms of species studied although there were significant differences in Et-OH extractive content, holocellulose and alpha-cellulose content among Malaysian bamboo studied. The ash content value of Malaysian bamboo is 5.43% to 8.50%. Malaysian bamboo has fiber crystallinity of 44.4%, 43.2%, 42% and 43.3% respectively for Semantan, Beting, Lemang, and Akar…